The Effect of Entertainment in Newspaper and Television News Coverage - Tanja Greiner (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
In this paper, we analyze the equilibrium amount of entertainment in news coverage of newspapers and television stations. We find that a shift in the inclination to read, expressed by a shift in the (psychological) distance costs, induces both media outlets to incorporate more entertaining elements in news coverage. The introduction of commercial television, however, which leads to a unilateral fall in the distance costs to the television broadcast, yields different results. It induces a negative effect on the profits of both media outlets, and increases price competition. Furthermore, the newspaper offers less while the television channel offers more entertainment. Overall, this leads to a marginalization of informational content, as the television channel gains market shares at the expense of the newspaper.
urn:nbn:de:bvb:19-epub-11551-9
Keywords: D72; L13; L82; 330; media economics; industrial organization; media bias; horizontal product differentiation; duopoly; Zeitung; Fernsehen; Duopol; Produktdifferenzierung; Event-Marketing; Wettbewerb; Mediennutzung; Medienökonomik; Industrieökonomik; Theorie